2021
DOI: 10.1007/s11121-021-01227-6
|View full text |Cite|
|
Sign up to set email alerts
|

Does Training Modality Predict Fidelity of an Evidence-based Intervention Delivered in Schools?

Abstract: Training prior to implementing evidence-based interventions (EBIs) is essential to reach high levels of fidelity. However, the time and cost of in-person training are often barriers to implementation. Online learning offers a potential solution, though few studies examine the relationship between online training and fidelity of implementation. This study explored whether teachers trained online have similar levels of adherence, dosage, quality of delivery, and student responsiveness compared to teachers traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
2
4
0
2
Order By: Relevance
“…Our study found that teachers who received inperson training and those who had higher-rated school coordinator and mentor support implemented greater numbers of core activities of FOYC + CImPACT, which underscores the critical role of these strategies in successful implementation of school-based HIV prevention programs. Consistent with findings from previous studies (Combs et al, 2021;Drake et al, 2015), our study found that teachers who received in-person training or both in-person and online training achieved the highest degree of implementation fidelity, followed by teachers who received online training only, and those who received no training performed the worst. Although teachers received curriculum information, models of core activities of the curriculum, and didactic sessions during the online training, they did not participate in role-plays, experiential practices, and teach-backs, which were available in in-person training.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study found that teachers who received inperson training and those who had higher-rated school coordinator and mentor support implemented greater numbers of core activities of FOYC + CImPACT, which underscores the critical role of these strategies in successful implementation of school-based HIV prevention programs. Consistent with findings from previous studies (Combs et al, 2021;Drake et al, 2015), our study found that teachers who received in-person training or both in-person and online training achieved the highest degree of implementation fidelity, followed by teachers who received online training only, and those who received no training performed the worst. Although teachers received curriculum information, models of core activities of the curriculum, and didactic sessions during the online training, they did not participate in role-plays, experiential practices, and teach-backs, which were available in in-person training.…”
Section: Discussionsupporting
confidence: 91%
“…In a national dissemination of an EBI on substance use and violence reduction for middle school students, Combs et al (2021) found that teachers trained online had similar levels of implementation fidelity measures, such as dosage delivered, adherence to the curriculum, and student responsiveness; however, the quality of delivery was lower than among teachers trained in-person. Becker et al (2014) found that teachers trained online achieved similar implementation quality and frequency of intervention delivery as those trained in-person.…”
Section: Delivery Modalities Of Teacher Training (In-person Vs Online)mentioning
confidence: 99%
“…Other researchers have had similar findings regarding online training. Researchers trained teachers to implement a life skills EBI through in-person or virtual modalities and found that those who received only online training rated the quality of the training lower, but the implementation quality in their classrooms did not differ from those that attended in-person trainings [ 40 ]. Thus, online training has the potential to be just as effective in preparing teachers to implement an EBI, and it affords more flexibility for teachers and trainers to attend safely, at their convenience (if the material is available asynchronously), and/or save travel costs, all of which provide a level of flexibility to mitigate barriers posed by crises.…”
Section: Discussionmentioning
confidence: 99%
“…Prog rammi toetuse tasandil on oluliseks osutunud näiteks õpetaja ja mentori koostöö kvali teet (Ransford et al, 2009;Wehby et al, 2012) ning metoodika kasutamise mudeldamine (Becker et al, 2013;Johnson et al, 2018). Kooli tasandil on leitud seoseid üldise koolikliimaga (Beets et al, 2008), juhtkonna toega (Combs et al, 2021;Ransford et al, 2009) ja suhete kvaliteediga kooli kollektiivis ( Gregory et al, 2007;Malloy et al, 2015). Õpetaja tasandil on leitud, et programmi rakendamise kvaliteeti mõjutavad psühholoogilised ressursid, näiteks läbi põlemine (Domitrovich et al, 2015;Musci et al, 2019).…”
unclassified
“…Oluline on ka suhtumine SEpädevuste õpetamisse laiemalt (Beets et al, 2008;Malloy et al, 2015). Õpilaste tasandit on vaadatud vähim: on selgu nud, et programmide kasutamise kvaliteeti on mõjutanud õpi laste sotsiaalmajanduslik taust (Combs et al, 2021(Combs et al, , 2022. Samuti on leitud, et kvaliteeti mõjutab ebasobiva või agressiivse käitumise esialgne määr klassis (Combs et al, 2022;Musci et al, 2019).…”
unclassified